2022
DOI: 10.3390/cancers14133269
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral Impairment in Pediatric Brain Tumor Survivors: A Meta-Analysis

Abstract: Purpose: The neurocognitive outcomes of pediatric brain tumor survivors have been extensively studied but the risk and predictors for neurobehavioral impairment are less clearly defined. We systematically analyzed the rates of emotional, psychosocial, and attention problems in pediatric brain tumor survivors. Methods: PubMed, Web of Science, Embase, Scopus, and Cochrane were searched for articles published between January 2012 to April 2022. Eligible studies reported neurobehavioral outcomes for PBTS aged 2 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 103 publications
(110 reference statements)
0
2
0
Order By: Relevance
“…During the post-treatment period, major learning disabilities are noted, with delays in passing grade exams, significant difficulties in numeracy and reading, and an impact on physical education [6,19,34]. Plus, a meta-analysis conducted by Wang et al in 2022 reported a higher rate of attention problems, emotional difficulties and psychosocial problems in pediatric brain tumor survivors [35]. Indeed, social inclusion with pairs remains a challenge for CCSs with CNS tumors, who are likely to have no close friends and therefore, can suffer from psychological distress [18,36].…”
Section: Risk Factors Of School Difficultiesmentioning
confidence: 99%
“…During the post-treatment period, major learning disabilities are noted, with delays in passing grade exams, significant difficulties in numeracy and reading, and an impact on physical education [6,19,34]. Plus, a meta-analysis conducted by Wang et al in 2022 reported a higher rate of attention problems, emotional difficulties and psychosocial problems in pediatric brain tumor survivors [35]. Indeed, social inclusion with pairs remains a challenge for CCSs with CNS tumors, who are likely to have no close friends and therefore, can suffer from psychological distress [18,36].…”
Section: Risk Factors Of School Difficultiesmentioning
confidence: 99%
“…Many children with brain tumours experience neurocognitive effects at some point in their disease course, resulting in dysfunction in domains of cognition, emotion, and behaviour. The estimated risk for children with brain tumours of having emotional, psychosocial, and attention problems are 15%, 12% and 12% respectively, according to a recent meta-analysis [9]. Even at 10-year survival, these patients still demonstrate neuropsychological and psychosocial impairment across multiple domains [10].…”
Section: Introductionmentioning
confidence: 99%